De-risking opportunities for banks: Examining productivity of sectoral bank credit flows - Samuel Kiemo; Camilla Talam (Kenya Bankers Association (KBA), 2019)
The recent technological advancement and financial innovations, competition from nonbank financial institutions and Mobile Network Operators (MNOs), challenging operating environment in addition to regulatory changes continue to exert pressure for banks in Kenya to modify their business operation models to adapt. Part of this modification emerging strategy involves banks undertaking de-risking actions to minimize the vulnerabilities to cope with risks posed by changing business dynamics. Banks can de-risk by investing in risky assets that provide high returns in their portfolio, such that the high returns compensate for the risk taken. This paper aims to explore the aspect of de-risking by considering how productivity of sectoral bank credit can provide a de-risking opportunity for banks in the long run by leveraging on inter-sectoral linkages that promote growth thus a high return and risk diversification for banks. Using quarterly data for the period 2009 to 2018, the paper applied VAR, VECM methodology. Our findings suggest significant intersectoral linkages between agriculture, industry and service sectors. The study finds services sector as the key sector that links all three sectors through which intersectoral linkages persist. Sectoral bank credit positively influence output not only in the sector where it is allocated but also to other sectors. We also find evidence of resource competition between the three sectors which affirms the extent of inter-sectoral linkages and their amplifying effect of inputs such as credit on growth and productivity.
Keywords: 330